Raw Material Inventory Analysis Using The Eoq (Economy Order Quantity) Method In Lebong Coffee Business In Lebong Utara District - Midas, Faisal; Susanti, Neri; Fitriano, Yun (Journal of Management, Economic, and Accounting, 2025)
The purpose of this study is to analyze raw material inventory using the EOQ (economy order quantity) method at Lebong Coffee Business in Lebong Utara District. This study focuses more on the analysis of raw material inventory of coffee beans for making ground coffee used at Lebong Coffee Business in Lebong Utara District from January 2023 to December 2023. The analysis methods used are Economic Order Quantity (EOQ), Reorder Point (ROP) and safety stock (SS). To meet the raw material needs of 13,250 kg during January 2023 to December 2023, the amount of coffee bean raw material purchases that must be made by Lebong Coffee Business in Lebong Utara District so that storage costs can be minimized is 944 kg each time a purchase is made with a purchase frequency of 14 times during one period (year). The safety stock that must be provided is 141 kg which is maintained in the warehouse to anticipate shortages of raw materials and can be used if there is a delay in orders so that the production process can continue. Reorders should be made when the inventory in the warehouse is 394 kg, with a lead time of 7 days so as not to hamper the company's production process.